Exegesis of the economic constitution - Chanamé Orbe, Raúl (2020)
The economic constitution is a creation of the 20th century and we have the Weimar Constitution as the pioneer and basis of this thought, its main contribution being the express acknowledgement of the content of the economy in a Constitution. In the particular case of the Peruvian Constitutions, although there were always economic and financial references in them, this can not always be understood in terms of an economic Constitution as an organic concept. While an important breaking point of the constitutional paradigm occurs in the Constitution enacted in 1920, the first of the 20th century, that establishes the beginning of social constitutionalism in Peru and which has an indirect impact on the economy and the capital; in essence, it is over the past 30 years that the principles that govern the economic system of the Peruvian Constitution such as social market economy, the liberty to enter into contracts, free competition, economic pluralism, equal capital treatment and consumer rights, among others, have been processed and updated